Comparsion Of VP9 And H265 Encoding Standards - Fendrich, Vítězslav (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2017)
This paper deals with a comparison of the latest VP9 and H.265 video compression standards by objective and subjective metrics. For this purpose, four short video sequences in Ultra High Definition (UHD) resolution and with various features are used. Quality of the compressed video sequences is evaluated by well-known objective video quality metrics and results are verified by subjective tests. Results revealed different efficiency of VP9 and H.265 encoders for various video contents.
Keywords: VP9; H.265; HEVC; PSNR; SSIM; VIFP; UHD; subjective test; MOS